THE ROLE OF MONGOLIA IN REGIONAL SECURITY - Munkh-Orgil Tuvdendarjaa (International Journal of Innovative Technologies in Social Science, 2024)
The situation in Northeast Asia is an important topic of international security arena. Political and economic relations between Russia and China, as well as the Korean Peninsula issue, which can have a major impact in Northeast Asia as such powerful actors that can change the world order and security environment. Past decades, the peace policy of mutual trust between the countries of the Northeast Asian region has become the most important issue not only in the regional but also in the international security environment. Therefore, it is important to analyze and assess a strategic interests and international geopolitical ambition of major powers that could directly or indirectly affect Mongolia's national security to develop national strategic solutions to enhance Mongolia’s national security and its security environment. Mongolia has no territorial, economic, military or political conflicts of interest with any of the countries in the region. Such reasons can give Mongolia an opportunity to be a key player in confidence-building measures to prevent hostilities, to avert escalation, to reduce military tension in Northeast Asia. There are many ways and fields to operate as peace player in this region. For instance, Mongolia can be an initiator or a main actor of a regional peacekeeping cooperation organization in Northeast Asia.